SURGICAL OUTCOMES IN EYES WITH EXTREMELY HIGH MYOPIA FOR MACULAR HOLE WITHOUT RETINAL DETACHMENT. Issue 10 (October 2018) - Wu, Tsung-Tien; Kung, Ya-Hsin; Chang, Chih-Yao; Chang, Shu-Ping
Abstract : Purpose: The authors evaluated surgical outcomes in eyes with extremely high myopia for macular hole (MH) without retinal detachment. Methods: In this retrospective study, 14 eyes with axial lengths of ≥30.0 mm underwent vitrectomy and internal limiting membrane (ILM) peeling with or without inverted ILM flap insertion for MH without retinal detachment (October 2009–June 2016). Outcome measures were MH closure confirmed by optical coherence tomography, best-corrected visual acuity, and complications. Results: The mean axial length was 30.69 ± 0.76 mm. The overall final closure rate was 85.7% (12/14 eyes); the mean follow-up was 17.29 (±20.20) months. Primary anatomical MH closure after 1 operation was achieved in three of eight eyes (37.5%) without an inverted ILM flap and was achieved in six of six eyes (100%) with inverted ILM flap insertion ( P = 0.031). There was no reopening of MH during follow-up. Mean visual acuity improved significantly from 1.10 ± 0.43 logarithm of the minimum angle of resolution (Snellen equivalent, 20/254) to 0.84 ± 0.50 logarithm of the minimum angle of resolution (Snellen equivalent, 20/138) ( P = 0.046; 2-tailed, paired t -test). Only 1 eye developed an MH-associated retinal detachment 4.5 years after previously failed MH surgery; reattachment was achieved after a second operation. Conclusion: Patients with extremely high myopia obtained anatomical and functional improvements from MH surgery; inverted ILM flap insertion achieved significantly higher primary success rates in MH closure. Abstract : Patients with extremely high myopia obtained anatomical and functional improvements from macular hole surgery; inverted internal limiting membrane flap insertion achieved significantly higher primary success rates in macular hole closure, without reopening during follow-up.